2019
DOI: 10.1016/j.legalmed.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Ion S5™ and MiSeq FGx™ sequencing platforms to characterize challenging human remains

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…In this study, DNA quantity and quality of the skeletal remain samples were assessed for library preparation during MPS run and STR allele recovery. Our data showed that the number of STR loci recovered was correlated with DNA input in the first round of PCR for samples <100 pg, which was also reported previously [10], which may be related to the library yield generated from the starting materials. DNA analysis using a low template DNA may still be a challenge in MPS‐based STR analysis similar to CE system.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, DNA quantity and quality of the skeletal remain samples were assessed for library preparation during MPS run and STR allele recovery. Our data showed that the number of STR loci recovered was correlated with DNA input in the first round of PCR for samples <100 pg, which was also reported previously [10], which may be related to the library yield generated from the starting materials. DNA analysis using a low template DNA may still be a challenge in MPS‐based STR analysis similar to CE system.…”
Section: Discussionsupporting
confidence: 88%
“…The recovery rate of STR alleles in the in‐house MPS‐STR system was dependent on the amplicon size (Supporting Information Fig. S5), as shown in the CE system, but not for all STR loci detected in previous studies [9, 10]. Overall, a higher success rate of recovery was obtained using the in‐house MPS‐STR system (mean 57.4 ± 15.2 samples, min.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Several commercial sequencing panels were developed for human identification, including the ForenSeq TM DNA Signature Prep Kit (Verogen V R , San Diego, CA, USA), the Precision ID GlobalFiler NGS STR Panel (Thermo Fisher Scientific, Waltham, MA, USA), and the PowerSeq TM 46GY System (Promega, Madison, WI, USA). These assays were tested rigorously by different forensic genetic laboratories, and they produced sequencing results that were concordant with CE-based STR typing assays at a level of sensitivity that is comparable to that of the currently used PCR-CE methods [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale performances and functional tests had been widely validated for the ForenSeq™ DNA Signature Prep Kit, the DNA Primer Set A (DPMA, 152 loci totally: 27 common, forensic autosomal STRs, 24 Y-STRs, 7 X-STRs, and 94 identity informative SNPs) and the DNA Primer Set B (in total 230 loci: DMPA plus 22 phenotypic informative SNPs and 56 biogeographical ancestry SNPs), which also include robustness, reproducibility, species specificity, consistency and sensitivity of detection [40][41][42][43][44][45][46][47]. In addition, the applicability of the DNA Signature Prep Kit had been evaluated and verified on challenging samples, DNA mixture, degradative DNA [48][49][50], formalin-fixed paraffin-embedded tissues [49,51], and remains of skeletons and bones [48,[52][53][54], to extend the applications for forensic sciences [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Hence, on the basis of the sufficient validations of the stability and homogeneity, more essential data of worldwide populations are needed urgently at present to improve the standard experimental procedures, promote the efficiencies of MPS-based system, and strengthen and unify the contacts between capillary electrophoresis-based (CE-based) and MPS-based data for the basic and extended applications of forensic sciences and others.As the aborigines in Hainan island where was the entrances to East Asia (either the southern entrance from Indo-China peninsula or the northern entrance from Central Asia) [12,[69][70][71], Hainan...…”
mentioning
confidence: 99%